THE EFFECT OF SACCHAROMYCES SPP PROBIOTICS IN FEED LAYING HENS TO INCREASE FEED DIGESTIBILITY AND REDUCE AMMONIA GAS CONTENT IN EXCRETA - I G. N. G., Bidura (Majalah Ilmiah Peternakan, 2020)
This study aims to examine the effect of adding probiotic Saccharomyces spp.N-2 (isolates from yeast tape) into the rations of laying hens to increase feed digestibility and reduce the amount of ammonia gas in excreta. One hundred twenty laying hens aged 40 weeks were used in a complete randomized design (CRD) study with four treatments and six replications. The four types of treatment, namely: ration without the provision of probiotics as a control (A); ration with the addition of 0.10% Saccharomyces spp.N-2 (B); ration with 0.20% Saccharomyces spp.N-2 (C); and rations with 0.30% Saccharomyces spp.N-2 (D). The results showed that the digestibility of dry matter, organic matter, and crude protein increased significantly (P<0.05) in chickens of group B, C and D. Among the treatments of group B, C, and D, there was no significant difference (P>0.05). The number of Choliform bacteria, E. coli in the digestive tracts of chicken in Group B, C, and D, significantly (P<0.05) decreased compared to controls (Group A). Likewise, ammonia gas (N-NH3) levels in chicken excreta decreased significantly (P<0.05) with the presence of probiotic supplementation in the ration. It was concluded that the addition of 0.10-0.30% Saccharomyces spp.N-2 probiotics in the ration could increase the digestibility of the ration, as well as reduce the content of E. coli bacteria and ammonia gas in the excreta in Lohmann Brown laying hens.